Pemanfaatan Realtime Database di Platform Firebase pada Aplikasi E-Tourism Kabupaten Nabire - Edwin Adrin Wihelmus Sanad; Andani Achmad; Dewiani Dewiani (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2018)
Tourism objects in the district of Nabire relatively not developed much and has not been handled optimally due to lack of promotion. E-Tourism which is an electronic application for the tourism sector that can facilitate the user to visit a tourist site at a location. The currently available apps can not make real-time data changes regarding the position of the app's user coordinates to find out where to find the sights. This study aims to provide information to application users about the position of the location of the tour and the position of users who can change in real-time using firebase. This research uses experimental method, that is pinned firebase platform on E-Tourism so that application can utilize various real-time database feature in firebase. The system is tested by moving the user's position of the app to see changes in position data in real-time and will be shown on the application map. The next test by showing the location of tourism as well as the path traveled by the user to reach the sights. The results of this study show the position of the user that can change in real-time when the user to switch position without having to refresh the data manually (refresh). Applications can also display a list of tourist sites and the path taken to get to the tourist sites located in Nabire district.